EFFECT OF ADDITION OF CARRAGEENAN CONCENTRATION ON QUALITY OF BREADFRUIT (Artocarpus atili) AND CANNABIS (Canna edulis) WET NOODLES - Ari Kristiningsih; Khoeruddin Wittriansyah; Sari Widya Utami; Santi Purwaningrum (BPFP Faperta UNIB, 2022)
Excessive consumption of gluten can cause disturbances in the digestive system and can increase intestinal permeability. Breadfruit flour is an alternative in making wet noodles other than wheat flour which is low in gluten. Breadfruit flour which is processed into wet noodles has low adhesion and protein content.Canna flour and carrageenan were used to improve adhesion and squid ink and eggs were used to increase the protein content of breadfruit noodles. This study aimed to determine the effect of adding carrageenan with different concentrations on breadfruit noodles. The ratio of addition of carrageenan in this research was 0%,1%, 3%, 4%, and 5%. Carrageenan in breadfruit noodles causes the noodles break more easily than noodles without the addition of carrageenan. The use of eggs and squid ink on breadfruit noodles increased the protein content of noodles by ± 1.1%.The results of the proximate analysis of breadfruit noodles as a whole still do not reach the SNI standard for wet noodles.